Cellular characterisation of magnetic resonance imaging bone oedema in rheumatoid arthritis; implications for pathogenesis of erosive disease. Issue 2 (2nd September 2008) - Dalbeth, N; Smith, T; Gray, S; Doyle, A; Antill, P; Lobo, M; Robinson, E; King, A; Cornish, J; Shalley, G; Gao, A; McQueen, F M
Abstract : Objectives: Magnetic resonance imaging (MRI) bone oedema is an important predictor of bone erosion in rheumatoid arthritis (RA). This study aimed to determine the cellular components of MRI bone oedema, and clarify the relationship between bone erosion and MRI bone oedema. Methods: Twenty-eight bones from 11 patients with RA undergoing orthopaedic surgery were analysed by quantitative and semi-quantitative immunohistochemistry. Pre-operative contrast-enhanced MRI scans were analysed for bone oedema. Results: The density of osteoclasts was higher in those samples with MRI bone oedema than those without MRI bone oedema (p = 0.01). Other cells identified within bone marrow included macrophages and plasma cells, and these were more numerous in samples with MRI bone oedema (p = 0.02 and 0.05 respectively). B cells were present in lower numbers, but B cell aggregates were identified in some samples with MRI bone oedema. There was a trend to increased RANKL expression in samples with MRI bone oedema (p = 0.09). Expression of RANKL correlated with the number of osteoclasts (r = 0.592, p = 0.004). Conclusions: The increased number of osteoclasts and RANKL expression in samples with MRI bone oedema supports the hypothesis that bone erosion in RA occurs through activation of local bone resorption mechanisms within subchondral bone as well as through synovial invasion into bone.